2017
DOI: 10.1371/journal.pone.0184515
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the human salivary microbiome diversity in Indian populations

Abstract: The importance of studying the salivary microbiome has been highlighted for its connection to health and disease and as a potential tool for supplementing human genetic diversity studies. While the salivary microbiome has been studied in various world populations, Indian populations have not been examined. We therefore analyzed microbiome diversity in saliva samples from 92 volunteers from eight different sampling locations in India by amplifying and sequencing variable regions (V1 and V2) of the bacterial 16S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…A particular signature of ethnicity in oral microbiome was also underlined by Sarkar et al [ 28 ] in 2017, when they analysed microbiome diversity in saliva samples collected from 92 healthy volunteers, coming from eight different geographical locations in India. These different locations represented three geographic regions in India.…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…A particular signature of ethnicity in oral microbiome was also underlined by Sarkar et al [ 28 ] in 2017, when they analysed microbiome diversity in saliva samples collected from 92 healthy volunteers, coming from eight different geographical locations in India. These different locations represented three geographic regions in India.…”
Section: Resultsmentioning
confidence: 83%
“…The lack of complete and wider information collection in experimental studies could compromise the possibility of gathering really informative data (i.e., useful to identify likely suspects in forensic contexts) from saliva microbiome analysis. For example, several studies published up till now have shown that salivary microbial composition can be related to the similar socio-economic background, culture, lifestyle, and food habits, which often characterize people coming from the same region [ 25 , 26 , 27 , 28 ]. In fact, factors such as food habits, which vary between different geographical locations, could contribute to the shaping of microbiome composition.…”
Section: Discussionmentioning
confidence: 99%
“…MiRnome and microbiome dysregulation in saliva of ASD patients was previously reported by other groups, but there is only a partial concordance with the data presented here [ 47 , 59 , 60 , 61 ]. The salivary microbiome structure in human beings is strongly affected by the geographical, climatic and ethnic origin of samples [ 62 , 63 , 64 ]. This could be due to the different ratio of dietary protein/ carbohydrate intake that, in turn, modulates salivary pH [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies found a high abundance of the phyla Firmicutes, Proteobacteria, Bacteroidetes, and Actinobacteria, with Streptococcus (belonging to the phylum Firmicutes) being the most abundant genus [ 60 , 61 ]. The presence of Verrucomicrobia in the oral cavity is often not described [ 60 , 61 , 62 , 63 , 64 ]. However, the presence of Akkermansia -like sequences was found in the oral cavity of a choledocholithiasis patient [ 65 ].…”
Section: Akkermansia Muciniphila Along the Humamentioning
confidence: 99%